Impact of recipient ABH secretor status on outcome in minor ABO‐incompatible hematopoietic stem cell transplantation. Issue 1 (2nd July 2014) - Holbro, Andreas; Stern, Martin; Infanti, Laura; O'Meara, Alix; Drexler, Beatrice; Frey, Beat M.; Tiercy, Jean‐Marie; Passweg, Jakob R.; Gassner, Christoph; Buser, Andreas; Sigle, Joerg‐Peter
<x xml:space="preserve">Abstract</x> Background The impact of ABO incompatibility on hematopoietic stem cell transplantation (HSCT) outcome is controversial. As ABH substances are expressed on tissues and secreted in body fluids, they could drive an immune response in minor ABO‐incompatible HSCT. The aim of the study was to investigate the prognostic role of the recipients' ABH secretor status. Study Design and Methods Patients who underwent minor ABO‐incompatible HSCT were included. Secretor status was determined either serologically or by molecular genetics. Results Between March 1996 and June 2012, a total of 176 patients received minor ABO‐incompatible HSCT and 150 (85%) were secretors. Incidence and severity of acute graft‐versus‐host disease (GVHD) and chronic GVHD did not differ between secretors and nonsecretors (cumulative incidences ± standard errors: acute GVHD on Day 100, 41 ± 11 and 46 ± 5%, p = 0.59; chronic GVHD at 2 years, 52 ± 13 and 56 ± 5%, p = 0.62, for secretors and nonsecretors, respectively). Additionally, nonrelapse mortality (NRM) and overall survival (OS) were similar in the two groups (2‐year NRM, 27 ± 9 and 23 ± 3%, p = 0.45; 4‐year OS, 64 ± 10 and 55 ± 4%, p = 0.28, for secretors and nonsecretors, respectively). Conclusion The recipients' ABH secretor status in minor ABO‐incompatible HSCT has no prognostic impact on major transplant outcomes.